AN INVESTIGATION OF COGNITIVE AND METACOGNITIVE STRATEGY USE: CHANGES AND DIFFERENCES - Meihua Liu (Universitas Katolik Indonesia Atma Jaya, 2009)
This paper reports on the results of a study of the use of cognitive and metacognitive strategies in English learning in terms of changes and differences during a term at the tertiary level in Chinese EFL contexts. A 35-item survey involving 934 undergraduate non-English majors revealed that: (1) the whole participant sample, as well as males and females, reported a low use of the cognitive strategies of practicing and creating structure for input and output but generally a medium use of the other cognitive and metacognitive strategies both at the beginning and toward the end of the term; (2) towards the end of the term, the whole sample, as well as males and females and the three university samples, tended to utilize significantly more frequently most of the cognitive and mecognitive strategies but less frequently the strategies of centering one’s learning; (3) significant differences occurred in the strategies of creating structure for input and output, centering one’s learning, and evaluating one’s learning between male and female students at the beginning and/or toward the end of the term, and in almost all the categories of cognitive and metacognitive strategies among the three university samples both at the beginning and toward the end of term; (4) the three university samples demonstrated differing patterns in using the cognitive and metacognitive strategies both at the beginning and toward the end of term. Based on the results, some implications and suggestions for future research are discussed.Keywords: Strategy use, cognitive, metacognitive, change, gender; context.